Mexican postage stamp commemorating Aniversario Petróleos Mexicanos (20th anniversary) - Mexico. Dirección General de Talleres de Impresión de Estampillas y Valores (1958)
Mexican postage stamp issued to commemorate the 20th anniversary of the nationalization of all petroleum reserves, facilities, and foreign oil companies in Mexico and the establishment of the state-owned petroleum company Petróleos Mexicanos. The stamp features an illustrated depiction of an oil refinery.
Keywords: Commemorative postage stamps; Mexico; Postage stamps; Science on postage stamps; Petroleum refineries; Petroleum industry and trade; Petroleum industry and trade--Government ownership; Petróleos Mexicanos